Parasite-Produced MIF Cytokine: Role in Immune Evasion, Invasion, and Pathogenesis - Ghosh, Swagata; Jiang, Nona; Farr, Laura; Ngobeni, Renay; Moonah, Shannon (Frontiers in Immunology, 2019)
Protozoan parasites represent a major threat to health and contribute significantly to morbidity and mortality worldwide, especially in developing countries. This is further compounded by lack of effective vaccines, drug resistance and toxicity associated with current therapies. Multiple protozoans, including Plasmodium, Entamoeba, Toxoplasma, and Leishmania produce homologs of the cytokine MIF. These parasite MIF homologs are capable of altering the host immune response during infection, and play a role in immune evasion, invasion and pathogenesis. This minireview outlines well-established and emerging literature on the role of parasite MIF homologs in disease, and their potential as targets for therapeutic and preventive interventions.